2017
DOI: 10.1039/c7sm01157a
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and electrorheological behavior of bowl-like titanium oxide nanoparticles

Abstract: Bowl-like titanium oxide nanoparticles were successfully prepared by a simple solvothermal method using absolute ethanol and isopropanol as the cosolvent. Ostwald ripening coupled with the inner-stress-induce effect were assumed to play an important role in the formation of this unique bowl-like morphology. The morphological evolution from solid nanosphere to bowl-like nanoparticle was investigated by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Besides, the structural charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Generally, interfacial polarization is mostly responsible for the formation of the internal structures in the ER suspensions. For a strong ER effect, ER fluids should require dielectric relaxation peak in ɛ″ between 100 and 10 5 Hz, and then have a large Δɛ′ (Δɛ′ = ɛ′ 100 Hz – ɛ′ 100 kHz ) . To gain more insight into the relationship of ER behavior with dielectric property, the permittivity (ɛ′) and dielectric loss factor (ɛ″) were investigated by broadband dielectric spectroscopy (Figure ) for PANI‐1mLPPy and PANI‐2mLPPy copolymers based ER fluid, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, interfacial polarization is mostly responsible for the formation of the internal structures in the ER suspensions. For a strong ER effect, ER fluids should require dielectric relaxation peak in ɛ″ between 100 and 10 5 Hz, and then have a large Δɛ′ (Δɛ′ = ɛ′ 100 Hz – ɛ′ 100 kHz ) . To gain more insight into the relationship of ER behavior with dielectric property, the permittivity (ɛ′) and dielectric loss factor (ɛ″) were investigated by broadband dielectric spectroscopy (Figure ) for PANI‐1mLPPy and PANI‐2mLPPy copolymers based ER fluid, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the unique advantages as discussed above, TiO 2 bowl-like nanomaterials also attract much interest from researchers. Chen et al reported a template-free method to produce bowl-like TiO 2 , [30] which is a typical solvothermal method with the following procedure: a proper amount of tetrabutyl titanate is dropped into a mixture of ethanol and isopropanol. Then, it is heated in a Teflon-lined stainless-steel autoclave for 6 h at 180 °C.…”
Section: Synthetic Strategies Of Bowl-like Nanostructuresmentioning
confidence: 99%
“…The researchers have made extensive studies on the electrorheological performance of titanium dioxide. [ 5,17,18 ] However, in the actual test process, we found that the ER performance of titanium oxide is not ideal and its density is high comparing with silicone oil. Therefore, many researchers began to prepare titanium oxide with different morphologies to improve its ER performance.…”
Section: Introductionmentioning
confidence: 99%